Operating Room Efficiency: Benefits of an Orthopaedic Traumatologist at a Level II Trauma Center. (December 2016) - Althausen, Peter L.; Kauk, Justin R.; Shannon, Steven; Lu, Minggen; O'Mara, Timothy J.; Bray, Timothy J.
Abstract : Objectives: Fellowship-trained orthopaedic traumatologists are presumably taught skill sets leading to "best practice" outcomes and more efficient use of hospital resources. This should result in more favorable economic opportunities when compared with general orthopaedic surgeons (GOSs) providing similar clinical services. The purpose of our study was to compare the operating room utilization and financial data of traumatologists versus GOSs at a level II trauma center. Design: Retrospective review. Setting: Level II community-based trauma hospital. Patients/Participants: Patients who presented to the emergency room at our institution with fractures and orthopaedic conditions requiring surgical intervention from January 1, 2010, to December 31, 2011. Intervention: Operative fracture fixation by members of our orthopaedic trauma panel, including fellowship and nontrauma fellowship-trained orthopaedic surgeons. Main Outcome Measurements: Our institutional database was queried to determine operative times, surgical supply and implant costs, and surgery labor expenses. Patients were stratified according to those treated by our trauma panel's 3 traumatologists and those treated by the 15 GOSs on our trauma panel. These 2 groups were then compared using standard statistical methods. Results: A total of 6449 orthopedic cases were identified and 2076 of these involved fracture care. One thousand one hundred ninety-nine patients were treated by traumatologists and 877 by GOSs. There was no statistical difference detected in American Society of Anesthesiologists score between trauma and nontrauma groups. Overall, the traumatologist group demonstrated significantly decreased procedure times when compared with the GOS group (55.6 vs. 75.8 minutes, P, 0.0001). In 16 of 18 most common procedure types, traumatologists were more efficient. This led to significantly decreased surgical labor costs (381.4 vs. 484.8; P < 0.0001) and surgical supply and implant costs (2567 vs. 3003; P < 0.0001). Conclusions: This study demonstrates that in our communitybased trauma system, fracture care provided by traumatologists results in improved utilization of hospital-based resources when compared with equivalent services provided by GOSs. Significantly decreased operative times, surgical labor expenses, and supply and implant costs by the fellowship-trained group represent enhanced control of the design, plan, execution, and monitoring of orthopaedic trauma care. Traumatologists can provide leadership recommendations for operating room efficiency in community-based orthopaedic trauma care models. Level of Evidence: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.